Impact of thyroid status on the response to ram effect in ewes - MENEGATOS (Ι. ΜΕΝΕΓΑΤΟΣ) J.; CHADIO (Σ. ΧΑΔΙΩ) S.; KALOGIANNIS (Δ. ΚΑΛΟΓΙΑΝΝΗΣ) D.; BAMBIDIS (Β. ΜΠΑΜΠΙΔΗΣ) V.; VALASI (Ε. ΒΑΛΑΣΗ) I.; CHRISTODOULOU (Β. ΧΡΙΣΤΟΔΟΥΛΟΥ) V.; KANTAS (Δ. ΚΑΝΤΑΣ) D. (Journal of the Hellenic Veterinary Medical Society, 2018)
The role of thyroid hormones on the transition to anestrous has been well established in ewes, but their possible involvement in the induction of reproductive activity remains obscure. The aim of the present study was to investigate the role of thyroid hormones in the induction of the first ovulation in relation to "ram effect" in ewes. Fourty-four ewes of the Greek Zackel mountain type breed were used. The ewes were housed separately from the rams until day 0 (entrance of rams). Blood samples were collected weekly for 4 weeks until 11 weeks after the ram entrance for the determination of thyroxin and progesterone levels. Thirty-five out of 44 ewes (group A) had a silent heat, while the rest 9 ewes (group B) exhibited a delayed estrus. Thyroxin levels rose immediately after ram entrance in animals of group A, but in group Β the increase in thyroid hormone levels was evident only after the first week. The difference in T4 levels between week 0 and 1 for ewes of group A was significantly higher than that observed for animals of group Β (p<005). The pattern of progesterone release was similar between the two groups, but a two week delay in the increase of progesterone concentration was observed in animals of group Β compared to group A. It is concluded that thyroid hormones may act at the beginning of the breeding season to cause a modification in gonadotrophin secretion leading to early ovulation.